A case of intraoperative arrest & mobile ECMO - Díaz Gómez Rodrigo Alejandro; Alvarado Neves Catalina; Karlezi de la Fuente Carmen Gloria; Bejarano Alva Gabriela Cecilia; Garcia Gomez Dafna; Rodas García Luisa Fernanda (The Journal of ExtraCorporeal Technology)
Over the past two decades, extracorporeal membrane oxygenation (ECMO) has been increasingly used to support critical patients with cardiac and respiratory failure who fail to respond to conventional management. In refractory cardiac arrest, ECMO can restore perfusion in patients who meet specific criteria designed to maximize survival benefit and good neurological outcomes. In recent literature, there is no report of mobile ECMO in a case of prolonged cardiac arrest with direct cardiac massage. We describe our experience with a 34-year-old man with multiple traumatic injuries following a motor vehicle collision. He was treated in a trauma center hospital in the same city as our center. He was initially in stable condition (spontaneous ventilation with FiO2 0.21, no vasoactive drugs, Glasgow 15, no acute kidney injury or other organ dysfunction). One week after admission, a retained left hemopneumothorax required surgical intervention, as previous drainage was ineffective. Computed tomography imaging was also concerning for parencyhmal injury by the thoracotomy tube. Intraoperatively, when the patient was placed in lateral position, he experienced cardiac arrest, presumed to be secondary to pulmonary embolism. After 18 min, we were asked to rescue this patient with ECMO, as he had no contraindications to support. After 81 min of advanced life support, including direct cardiac massage, return of spontaneous circulation was achieved seconds after ECMO was initiated. He was then transported to our hospital. The patient achieved a favorable neurological outcome (Glasgow Coma Scale score of 15 at 24 h) and was discharged after a 2 month stay. This case highlights the potential benefits of prolonged cardiopulmonary resuscitation and ECMO in patients with refractory in-hospital cardiac arrest. In this case, proper ACLS and CPR allowed time for mobile ECMO support to be initiated from a remote center.